2019
DOI: 10.1007/s13205-019-1701-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing oil accumulation in the oleaginous yeast Cystobasidium oligophagum JRC1 using dairy waste cheese whey as a substrate

Abstract: This study assesses the potential for the lipid production by the oleaginous yeast Cystobasidium oligophagum JRC1 using dairy industry waste cheese whey as a substrate. Cheese whey was used either untreated (UCW) or deproteinized (DCW) at different concentrations (25-100%) to serve as the carbon and energy source. Both UCW and DCW supported high biomass and lipid productivities. The biomass productivity of 0.076 ± 0.0004 and 0.124 ± 0.0021 g/L h, lipid productivity of 0.0335 ± 0.0004 and 0.0272 ± 0.0008 g/L h,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Cystobasidium oligophagum has been characterized to e ciently convert WP into lipid. The biomass and the lipid content were 43.1% and 6.38 g/L, respectively (Vyas et al, 2019). In another study, the biomass and lipid production of Cryptococcus curvatus from WP achieved 10.77 g/L and 63.4%, respectively (Carota et al, 2017).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Cystobasidium oligophagum has been characterized to e ciently convert WP into lipid. The biomass and the lipid content were 43.1% and 6.38 g/L, respectively (Vyas et al, 2019). In another study, the biomass and lipid production of Cryptococcus curvatus from WP achieved 10.77 g/L and 63.4%, respectively (Carota et al, 2017).…”
Section: Discussionmentioning
confidence: 92%
“…Generally, very few yeasts possess β-galactosidase and galactose metabolism pathway, thus resulting in the impossibility to utilize lactose by most yeasts (Domingues et al 2010). In previous studies, only two oleaginous yeasts have been reported able to accumulate lipid from WP with a content of more than 40% (Carota et al, 2017;Vyas et al, 2019). Cystobasidium oligophagum has been characterized to e ciently convert WP into lipid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that this strain can even convert xylose into lipid, which is quite challenging for many other yeasts [ 8 ]. Besides, it can utilize the sucrose, commonly used as a conventional carbon source, and galactose-based sugars in an efficient manner, revealing the existence of a developed galactosidase system [ 6 , 30 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Actually, A. namibiae was the first oleaginous microorganism reported to produce lipid using SM as the feedstock. In previous studies, only two oleaginous yeasts have been reported able to accumulate lipid from WP with a content of more than 40% [ 6 , 30 ]. Cystobasidium oligophagum has been characterized to efficiently convert WP into lipid.…”
Section: Discussionmentioning
confidence: 99%